Cognitive angle of «another sociality» - Zhussupova, B.Zh. (Ye.A.Buketov Karaganda State University Publ., 2018)
The article raises the problem of the study of modern society, explicitly represented by heterogeneous sociality. The power of the dynamics of modern life breaks the usual human connections, but, most importantly, the basic human landmarks. The main attributes of a heterogeneous society - the difference, the multiplicity of singularities, decentration. Decentration of the human community occurs. This is another nature, «another sociality», «another humanity». The modern course of social development demonstrates dissonance with the reductionist classical attitudes of social philosophy to the monotony and integrity of social being and proves their inconsistency, lifelessness and even inhumanity due to ignoring the quality of human life. What became important was the humanitarian character of thinking, which is designed to overcome the classical subjectobject mindset and get closer to subject-subject, to self-knowledge.
«Басқа əлеуметтіктің» когнитивті ракурсы
Когнитивный ракурс «другой социальности»
Keywords: heterogeneous society; post-nonclassical discourse; post-nonclassical methods; epistemological potential; cognitive interest; heterological paradigm; plurality of singularities; nonlinear structure; dynamics of self-development; human-like tactics